Analisis Bibliometrik berdasarkan Dalil Zipf pada Jurnal Kajian Informasi dan Perpustakaan Universitas Padjadjaran Tahun 2020-2024 - Bela, Salsa; Juvitasari, Prisca Budi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
Over the past five years, the Jurnal Kajian Informasi dan Perpustakaan has experienced a significant increase in the number of published articles. This growth has led to challenges in retrieving relevant information efficiently, highlighting the need for better information organization. One bibliometric approach that supports the organization and retrieval of information through keyword analysis and subject heading assignment is Zipf’s Law. This study aims to analyze word distribution, identify keywords located in the transition zone, assess the relevance between author-assigned keywords and those generated using Zipf’s indexing, and determine research topic trends based on Hawkins’ taxonomy. The research employs a quantitative approach using bibliometric analysis grounded in Zipf’s Law. Data analysis involves the application of Zipf’s Law I, Goffman's transition point formula, and subject classification using Hawkins’ taxonomy. The findings show that the word distribution and transition values vary across articles. Transition zone keywords are selected using a maximum range of 12 words above and below the identified transition point. Of the 82 articles analyzed, 48 (58%) showed keyword relevance, 33 (40%) showed marginal relevance, and only 1 article (1%) was found irrelevant. Subject trend analysis reveals that Societal Issues and Libraries and Library Services are the most prominent categories, each accounting for 28% of the total articles. This study demonstrates that Zipf’s Law can effectively generate relevant keywords and identify dominant research themes within scholarly publications. The results reinforce the potential of Zipf’s Law as a reliable tool for enhancing information retrieval and organizing subject classifications in academic journals